2018
DOI: 10.1080/03008207.2017.1408599
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic remodeling and modification to preserve skeletogenesis in vivo

Abstract: Current studies offer little insight on how epigenetic remodeling of bone-specific chromatin maintains bone mass in vivo. Understanding this gap and precise mechanism is pivotal for future therapeutic innovation to prevent bone loss. Recently, we found that low bone mass is associated with decreased H3K27 acetylation (activating histone modification) of bone specific gene promoters. Here, we aim to elucidate the epigenetic mechanisms by which a miRNA cluster controls bone synthesis and homeostasis by regulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Increased Histone H3K9 and H3K27 Acetylation and RUNX2 Occupancy Indicate Baf45a and Baf45d Promoters Are Highly Accessible During Induction of BMSCs to Osteoblast Differentiation Studies previously suggested that Baf45a associated chromatin remodeling facilitates neurogenic differentiation (28). We currently identified that Baf45a remodeled chromatin implicate the transcriptional activation of osteoblast-specific genes (37). Lately, we found that osteoblast-specific deletion of Baf45a reduced bone formation in vivo.…”
Section: Resultsmentioning
confidence: 70%
See 3 more Smart Citations
“…Increased Histone H3K9 and H3K27 Acetylation and RUNX2 Occupancy Indicate Baf45a and Baf45d Promoters Are Highly Accessible During Induction of BMSCs to Osteoblast Differentiation Studies previously suggested that Baf45a associated chromatin remodeling facilitates neurogenic differentiation (28). We currently identified that Baf45a remodeled chromatin implicate the transcriptional activation of osteoblast-specific genes (37). Lately, we found that osteoblast-specific deletion of Baf45a reduced bone formation in vivo.…”
Section: Resultsmentioning
confidence: 70%
“…Studies previously suggested that Baf45a associated chromatin remodeling facilitates neurogenic differentiation ( 28 ). We currently identified that Baf45a remodeled chromatin implicate the transcriptional activation of osteoblast-specific genes ( 37 ). Lately, we found that osteoblast-specific deletion of Baf45a reduced bone formation in vivo .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study performed to evaluate the epigenetic mechanisms of miR-23a in regulating bone synthesis and homeostasis, knockdown of the miR-23a cluster was shown to enhance osteogenic differentiation with decreased expression of EZH2 and increased expression of Baf45a, a factor responsible for increasing chromatin accessibility. This resulted in the induction of OC by increasing H3K27ac levels and decreasing H3K27me3 levels at the OC gene promoter 77 .…”
Section: Introductionmentioning
confidence: 99%